ELECTRICAL PLATFORM FOR DRIVE OF AC ASYNCHRONOUS MOTORS AND SERVOMOTORS USING FREQUENCY CONVERTERS - STAN, MIHAIL-FLORIN; FIDEL, NICOLAE; VASILE, NICOLAE (Journal of the sciences and arts, 2021)
The development of industrial automation has implicitly led to the improvement of electric drive systems, especially since such installations are the most common form of conversion of electricity into mechanical energy. The electric drive can be defined and studied only if we consider the whole assembly of which it is part, such as the automation of a technological production process. This paper describes the design and practical implementation of a laboratory stand with a teaching feature. The designed stand is a study support for various applications used in the industrial area, offering the possibility of experimentation on programming and parameterization of frequency converters in the laboratory of "Electrical machines and drives" of the Faculty of Electrical Engineering, Electronics and Information Technology at the University of Valahia from Targoviste.